2008
DOI: 10.1063/1.3023156
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of converging shock waves generated by underwater electrical wire array explosion

Abstract: Results of ∼200 kbar pressure generation at 50 μm distance from the implosion axis of the converging shock wave produced by an underwater electrical explosion of a cylindrical wire array are reported. The array was exploded using a submicrosecond high-current generator (stored energy of ∼4.2 kJ, current amplitude of ∼325 kA, rise time of ∼1 μs). Multiframe shadow imaging of the shock wave was used to determine its time of flight. These data were applied for calculating the pressure at the vicinity of the implo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…Nevertheless, in experiments with the explosion of a 5 mm in radius cylindrical wire array, azimuthal symmetry of converging SW down to a radius r % 100 lm was obtained by shadow imaging. In addition, the results of spectroscopy of the plasma formed inside a copper capillary placed coaxially inside the array indicate the axial and azimuthal symmetry of the cylindrical converging SW. 19 Recently, the results of two-dimensional HD simulations 23 showed that artificially introduced non-uniformity of the cylindrical converging SW should be self-repaired, which agrees with the Whitham model. 24 Self-similar analysis of the converging SW implosion 17 showed that the pressure p behind the SW front located at the radius r can be calculated at instant t as p ¼ p o ðr=r o Þ 2À2=a , where p 0 and r 0 are the pressure and radius, respectively, at some previous instant t 0 < t, and a is the self-similarity parameter that equals 0.75 and 0.6 for cylindrical and spherical SWs, respectively.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Nevertheless, in experiments with the explosion of a 5 mm in radius cylindrical wire array, azimuthal symmetry of converging SW down to a radius r % 100 lm was obtained by shadow imaging. In addition, the results of spectroscopy of the plasma formed inside a copper capillary placed coaxially inside the array indicate the axial and azimuthal symmetry of the cylindrical converging SW. 19 Recently, the results of two-dimensional HD simulations 23 showed that artificially introduced non-uniformity of the cylindrical converging SW should be self-repaired, which agrees with the Whitham model. 24 Self-similar analysis of the converging SW implosion 17 showed that the pressure p behind the SW front located at the radius r can be calculated at instant t as p ¼ p o ðr=r o Þ 2À2=a , where p 0 and r 0 are the pressure and radius, respectively, at some previous instant t 0 < t, and a is the self-similarity parameter that equals 0.75 and 0.6 for cylindrical and spherical SWs, respectively.…”
mentioning
confidence: 78%
“…16 This allows this approach for generating converging strong SW by underwater electrical explosion of either cylindrical of spherical wire arrays to be applied in order to obtain an extreme state of water in the vicinity of the SW implosion. 17,18 In the case of a cylindrical wire array explosion, shadow imaging of the generated SW and water light emission in the vicinity of the convergence axis were used to calculate the time-of-flight (TOF) of the SW. 19,20 These data and the $12% efficiency of the stored energy transfer to the converging water flow were used as validation parameters for comparison with the results of one dimension hydrodynamic (HD) simulations, coupled with the experimentally measured energy deposited into the wires and the EOS for water. 21 The results of these simulations showed that in the vicinity of the convergence axis, the values of pressure P % 4.7 Â 10 11 Pa, temperature T % 3 eV, and density q % 4 g/ cm 3 can be reached.…”
mentioning
confidence: 99%
“…[1][2][3] Different dynamic loading facilities, such as multi-stage light gas guns, 4 Z-pinch, 5 powerful lasers, 6,7 and intense heavy ion beams, 8 with a stored energy in the range of 10 5 -10 9 J, are required to generate extreme states of matter 9 characterized by a pressure P ! 10 11 Pa during a short (in the range 10 À9 -10 À6 s) time duration. Recent research [10][11][12] showed that by using a pulsed power generator with stored energy of only a few kJ as a current source for the underwater electrical explosion of a wire array, one can generate WDM with P 6 Â 10 12 Pa.…”
mentioning
confidence: 99%
“…10 11 Pa during a short (in the range 10 À9 -10 À6 s) time duration. Recent research [10][11][12] showed that by using a pulsed power generator with stored energy of only a few kJ as a current source for the underwater electrical explosion of a wire array, one can generate WDM with P 6 Â 10 12 Pa. This method exploits the converging strong shock waves (SWs) generated by the underwater electrical explosion of either a cylindrical or a spherical wire array.…”
mentioning
confidence: 99%
“…[1][2][3] Several approaches that require stored energy in the range of 10 5 -10 9 J, such as multi-stage light gas guns, 4 Z-pinch, 5 powerful lasers, 6,7 and intense heavy ion beams, 8 are used to generate this state of matter, 9 which is characterized by a pressure !10 11 Pa. Recent research 10,11 showed that underwater electrical explosion of a wire array can be used as an alternative method to generate warm dense matter with 2 Â 10 12 Pa, using generators with moderate (several kJ) stored energy. This method is based on the implosion of the converging strong shock wave (SSW) generated by the underwater electrical explosion of either cylindrical or spherical wire arrays.…”
mentioning
confidence: 99%